Impact of submarine groundwater discharge on biogeochemistry and microbial communities in pockmarks. (1st October 2022) - Purkamo, Lotta; von Ahn, Cátia Milene Ehlert; Jilbert, Tom; Muniruzzaman, Muhammad; Bange, Hermann W.; Jenner, Anna-Kathrina; Böttcher, Michael Ernst; Virtasalo, Joonas J.
Abstract: The impact of submarine groundwater discharge (SGD) on coastal sea biogeochemistry has been demonstrated in many recent studies. However, only a few studies have integrated biogeochemical and microbiological analyses, especially at sites with pockmarks of different degrees of groundwater influence. This study investigated biogeochemical processes and microbial community structure in sediment cores from three pockmarks in Hanko, Finland, in the northern Baltic Sea. Pockmark data were supplemented by groundwater and seawater measurements. Two active pockmarks showed SGD rates of 0.02 cm d −1 and 0.31 cm d −1, respectively, based on porewater Cl − profiles, while a third pockmark had no SGD influence. Reactive transport modelling (RTM) established that the porewater systems of these active pockmarks are dominated by advection, resulting in the focusing of biogeochemical reactions and the microbial community into a thin zone at the sediment surface. The advection further reduces the accumulation of organic matter in the surface sediments, resulting in the absence of a sulfate-methane transition zone (SMTZ) at these pockmarks. Furthermore, the RTM estimated low rates of consumption of SO4 2−, and low rates of production of CH4, NH4 +, DIC at the active pockmarks. Archaeal communities in the active pockmarks were dominated by ammonia-oxidizing archaea of predominantly groundwater origin. In contrast, at the inactive pockmark, the lack of SGD has permitted rapid deposition of organic-rich mud. The porewater system in the inactive pockmark is dominated by diffusion, leading to orders of magnitude higher metabolite concentrations at depth compared to the active pockmarks. The biogeochemical environment in the inactive pockmark resembles typical organic-rich mud seafloor in the area, with sulphate reduction and methanogenesis dominating organic matter remineralization. Accordingly, methanogens dominate the archaeal community, whereas sulfate reducers dominate the bacterial community. RTM results suggest that sulfate-mediated anaerobic oxidation of methane (S-AOM) also occurs at this site. Although depth-integrated fluxes of SO4 2−, CH4, NH4, DIC at the inactive pockmark are orders of magnitude higher compared to the active pockmarks, processes at the inactive pockmark represent internal recycling in the coastal sea. Fluxes observed at the active pockmarks, although comparatively small in magnitude, are partly influenced by external inputs to the sea through SGD. Hence, effluxes across the sediment–water interface at these sites partly represent direct external fluxes to the marine environment, in addition to diagenetic recycling at the benthic interface. The study highlights that SGD can result in significant spatial heterogeneity of biogeochemical processes and microbial community structure in the coastal zone, and that the overall effects of SGD and associated solute fluxes at an SGD site are a function of the number of pockmarks, the rate of SGD, and the ratio of active to inactive pockmarks.